PKM Production Improvement Rabbit Farmer Group in the Bedugul Tourism Area, Tabanan-Bali - Wirajaya, Anak Agung Ngurah Mayun; Yuliartini, Made Sri; Sanjaya, I Gusti Agus Maha Putra; Udayana, I Gusti Bagus; Mahardika, Ida Bagus Komang; Dusak, Putu Gede Janardhana; Putra, I Ketut Suwarmadi; Mertayasa, Komang Gede (Asian Journal of Community Services, 2024)
Bedugul tourist attractions with the lake and the attractive Beratan Temple, the "Eka Karya" Botanical Gardens, a place to enjoy impressive nature in Candikuning Village, are favorite tourist destinations for domestic tourists and foreign tourists visiting BaliMost of the people of Candikuning work in the agricultural sector as their livelihood and source of livelihood, requiring fertilizer to increase soil and plant fertility. Currently, most of the organic fertilizer used is chicken manure, which is purchased from outside the village, while the potential for developing rabbits in Candikuning Village as a potential source of fertilizer is still underutilized. The objectives of this activity for partners are: increasing partners' knowledge and skills in rabbit cultivation, using solid and liquid manure as organic fertilizer to substitute for the use of inorganic fertilizer, meeting increasing market demand by adding production facilities to support product quality, increasing quantity and continuous production.